Hubungan Frekuensi Senam Hamil dengan Kualitas Tidur Ibu Hamil di BPM Indri Sujarwo Demak - Rika Amelia; Agnes Istiharjanti; Danny Putri (STIKes Ibnu Sina Ajibarang, 2025)
Survey results from 97% of pregnant women in Indonesia and Central Java related to sleep disturbances in 2016 show that pregnant women in the second and third trimesters often wake up at night, and in the second and third trimesters, pregnant women often experience sleep disturbances. An increase in the gestational age of the mother causes this. Based on the results of a preliminary study conducted in January 2023 by the researcher at BPM (Independent Practice Midwife) Indri Sujarwo Demak on ten pregnant women who filled out a questionnaire, it was found that seven pregnant women experienced poor sleep quality and three pregnant women experienced good sleep quality. This study aimed to determine the relationship between the frequency of pregnancy exercise and the sleep quality of pregnant women. This type of research was observational, using an analytic survey method. The design of this study used a cross-sectional approach. The population in this study was all pregnant women who participated in pregnancy exercises with 50 students. Retrieval of data using a total sampling technique. The instrument used is the sleep quality questionnaire (PSQI). The statistical test used was the Chi-Square test. The results of the study were that there was a p-value of 0.000, so that the p-value (0.000) < α (0.05), it can be concluded that there is a relationship between the frequency of pregnancy exercise and sleep quality with an R-value of 0.619, which means that the level of the relationship is strong. It is hoped that this research can practice and expand information for pregnant women about the importance of attending pregnancy exercise classes and applying it at home so that pregnant women sleep better and reduce discomfort during childbirth.